EFSA and ECDC technical report on the collection and analysis of whole genome sequencing data from food‐borne pathogens and other relevant microorganisms isolated from human, animal, food, feed and food/feed environmental samples in the joint ECDC‐EFSA molecular typing database. Issue 5 (29th May 2019) - ,; ,; Van Walle, Ivo; Guerra, Beatriz; Borges, Vitor; André Carriço, João; Cochrane, Guy; Dallman, Tim; Franz, Eelco; Karpíšková, Renata; Litrup, Eva; Mistou, Michel‐Yves; et al.
Abstract : EFSA and ECDC were requested by the European Commission to jointly evaluate the possible solutions for the collection and analysis of whole genome sequencing (WGS) data for at least Listeria monocytogenes, Salmonella and Escherichia coli by: (1) analysing the outcome of the surveys on the status of the use of WGS of food‐borne pathogens in EU/EEA countries in both the food and public health sectors; (2) conducting a consultation of relevant actors to assess state‐of‐the‐art pipelines for collecting and analysing WGS data in Europe; (3) involving relevant stakeholders to assess the needs and requirements for the analysis of WGS data and their comparability; and (4) preparing a technical report on the identification and comparison of potential solutions for the set‐up and running of a joint EFSA‐ECDC pipeline to collect and analyse WGS data. Logical components of the overall system were identified and technical requirements were prioritised and grouped according to functionality. Eleven platforms (solutions) that integrate the relevant functionalities for collecting, analysing and visualising WGS data were thoroughly described. The degree to which the requirements are met by the different solutions (as of 31 December 2018) was evaluated. The assessment made clear that no single solution meets all the critical requirements and each solution has significant gaps regarding the unmet critical requirements. Therefore, scenarios consisting of a combination of several solutions were considered. As there may be many suitable scenarios, and the choice among them will depend on strategic or financial elements that are not within the scope of this report, it contains the scientific and technical elements necessary to generate scenarios, rather proposing individual scenarios. A scenario builder is presented which includes the significant gaps for each solution/functionality and the limitations and risks to be considered when setting up a joint ECDC‐EFSA database for the collection and analysis of WGS data.